2022
DOI: 10.1093/mutage/geac022
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution in Sarajevo, Bosnia and Herzegovina, assessed by plant comet assay

Abstract: Bosnia and Herzegovina (B&H) is among the European countries with the highest rate of air pollution-related death cases and the poorest air quality. The main causes are solid fuel consumption, traffic, and the poorly developed or implemented air pollution reduction policies. In addition, the city of Sarajevo, the capital of B&H, suffers temperature inversion episodes in autumn/winter months, which sustain air pollution. Human biomonitoring studies may be confounded by the lifestyle of subjects or possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, human biomonitoring remains the best approach for evaluating the effects of complex mixtures, providing data for further in vitro and in silico studies, and scientifically based risk assessment [ 72 , 73 , 74 , 75 ]. Recent studies suggest that sentinel organisms such as butterflies and plants, sensitive to air pollutants, could serve as early warning signs for human biomonitoring studies [ 76 , 77 , 78 , 79 ]. Future prospective studies should include biomarkers of air pollution exposure, human exposure conditions, and assessment of biomarkers of oxidative stress and inflammation, as these events might occur earlier in the exposure–effect scenario, forming a basis for DNA damage induction.…”
Section: Discussionmentioning
confidence: 99%
“…However, human biomonitoring remains the best approach for evaluating the effects of complex mixtures, providing data for further in vitro and in silico studies, and scientifically based risk assessment [ 72 , 73 , 74 , 75 ]. Recent studies suggest that sentinel organisms such as butterflies and plants, sensitive to air pollutants, could serve as early warning signs for human biomonitoring studies [ 76 , 77 , 78 , 79 ]. Future prospective studies should include biomarkers of air pollution exposure, human exposure conditions, and assessment of biomarkers of oxidative stress and inflammation, as these events might occur earlier in the exposure–effect scenario, forming a basis for DNA damage induction.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of deciduous plants can be used as bioindicators of the DNA damage caused by various genotoxic factors such as radiation, chemicals, allelochemicals, heavy metals, nanoparticles, or complex contaminants originating from the atmosphere and soil. Ligustrum vulgare (common privet) has been used as a model to monitor the air pollution using Comet assays: analyses of leaves harvested at three locations with different levels of air pollution in Bosnia and Herzegovina, including two urban and one rural location, showed that DNA damage measured as tail intensity depended on the sampling period, leaf position, and growth stage, and showed clear differences between urban and rural locations [147]. Furthermore, this model proved sensitive to seasonal variations in air pollution levels since DNA damage in L. vulgare leaves was proportional to the average concentration of particulate matter of a size ranging from 0.001 to 2.5 µm in diameter (PM 2.5 ) and depended on indoor vs. outdoor conditions [147].…”
Section: Comet Assays In Plant Ecotoxicology and Biological Monitoringmentioning
confidence: 99%
“…Temperature inversion, as a natural phenomenon, occurs when temperatures at higher altitudes are higher than temperatures at lower altitudes, causing pollutants to be stuck and leading to higher pollutant concentrations in the air. The problem of air pollution is one of the major problems in the city of Sarajevo, where the citizens often face excessive levels of air pollutants [1,2]. The problem of air pollution is particularly present in the winter period and the heating season in the months of November, December, January, February and March.…”
Section: Introductionmentioning
confidence: 99%